Exploring the emergence of an 'Aquatic' Neolithic in the Russian Far East: organic residue analysis of early hunter-gatherer pottery from Sakhalin Island. (6th December 2017) - Gibbs, Kevin; Isaksson, Sven; Craig, Oliver E.; Lucquin, Alexandre; Grishchenko, Vyacheslav A.; Farrell, Tom F.G.; Thompson, Anu; Kato, Hirofumi; Vasilevski, Alexander A.; Jordan, Peter D.
Abstract: Abstract : The Neolithic in north-east Asia is defined by the presence of ceramic containers, rather than agriculture, among hunter-gatherer communities. The role of pottery in such groups has, however, hitherto been unclear. This article presents the results of organic residue analysis of Neolithic pottery from Sakhalin Island in the Russian Far East. Results indicate that early pottery on Sakhalin was used for the processing of aquatic species, and that its adoption formed part of a wider Neolithic transition involving the reorientation of local lifeways towards the exploitation of marine resources.